Analisis Hukum Pembiayaan Mudharabah dalam Bisnis Mikro dan Kecil di Indonesia: Analisis Hukum Pembiayaan Mudharabah - Romlah; Kusyana, Kusyana (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2023)
Mudharabah financing is one of the significant financial instruments in the Islamic banking industry, especially in supporting micro and small businesses (MSBs) in Indonesia. This research aims to analyze the legal aspects of mudharabah financing in the context of micro and small businesses in Indonesia, including understanding the basic principles, implementation, challenges, and opportunities. The research method used is a qualitative approach with data collection through literature review and analysis of relevant documents. The research findings indicate that mudharabah financing has great potential in supporting the growth of MSBs in Indonesia, but it also faces several challenges, such as a lack of understanding of mudharabah principles and legal uncertainties. Recommendations are given to strengthen regulations, enhance understanding of mudharabah financing, and facilitate access to financing for micro and small business players. This research provides a significant contribution to stakeholders in understanding the role and potential of mudharabah financing in supporting the development of MSBs in Indonesia. Keywords: Mudharabah Financing, Micro and Small Businesses, Islamic Economic Law, Regulation, Indonesia.